2019
DOI: 10.13164/re.2019.0464
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum Sensing Based on Higher Order Cumulants and Kurtosis Statistics Tests in Cognitive Radio

Abstract: In this paper, new algorithms for spectrum sensing in cognitive radio based on higher order cumulants and kurtosis are proposed. The cumulants represent statistical signal processing based on pattern recognition for signals of different structure, and has low implementation complexity. Kurtosis statistics are a well-known technique for testing the Gaussianity feature of the signals. Under the assumption that a detected signal can be modelled according to an autoregressive model, noise variance is estimated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…, solving for the algebra of P f , the new threshold value is calculated as (13) where erfc(•) is the inverse of the well-known error function. In the same way, if the detection variable is greater than the threshold, the algorithm decides for H 1 ; otherwise, the choice is for H 0 .…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…, solving for the algebra of P f , the new threshold value is calculated as (13) where erfc(•) is the inverse of the well-known error function. In the same way, if the detection variable is greater than the threshold, the algorithm decides for H 1 ; otherwise, the choice is for H 0 .…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…Step3: Result of Step2 is used as training data to train and save the training model. Step4: Calculate the threshold using (13), if the detection function is 1, the primary user is detected; if the detection function is − 1, the primary user is not exist. Generate historical data with obtained values.…”
Section: Simulation Setting In This Section a Variety Of Montementioning
confidence: 99%
See 1 more Smart Citation
“…Method described in [21], which uses a fundamentally different basis of detection, is a benchmark adopted in the conducted research. The research covers the most frequently referenced GoF tests, indicated as those with high efficiency and superiority to other similar, i.e., Jarque-Bera (JB) [22]- [24] and higher-order statistics (HoS) [25], [26].…”
Section: Introductionmentioning
confidence: 99%
“…In general, non-Gaussian signals are processed based on higher-order statistics (HOS) or fractional lower-order statistics (FLOS) [9][10][11][12]. If these signals are incorrectly assumed to satisfy Gaussian distribution, the filter will perform poorly or cease to be effective [13], because these signals obey α-stable distribution rather than Gaussian distribution.…”
Section: Introductionmentioning
confidence: 99%